From Molecular Achirality to Mesoscopic Helicity: Toward the Development of Circularly Polarized Luminescence‐Emitting Liquid Crystal Displays. Issue 1 (9th September 2020) - Wu, Wenjie; Zhang, Jing; Song, Fengyan; Lam, Jacky Wing Yip; Tang, Ben Zhong
Abstract : Display devices with circularly polarized luminescence (CPL) can realize sophisticated functions. However, the generation of mesoscopic chirality and CPL is usually very difficult, especially for those devices fabricated from achiral molecules. Herein, a very simple device is fabricated by achiral twisted nematic liquid crystals (LCs) doped with achiral aggregation‐induced emission luminogens, which exerts high‐performance CPL through molecular assembly. Full‐colored CPL with relatively high luminescence dissymmetry factor of 10 −2 is achieved. This study thus not only provides new insights in constructing high‐performance CPL‐emitting devices but also promotes the development of LC display techniques. Abstract : The transformation from molecular achirality to mesoscopic helicity is successfully realized in simple twisted nematicity liquid crystal (LC) devices containing achiral LC and achiral aggregation‐induced emission luminogens. High‐performance and full‐colored circularly polarized luminescence with relatively high luminescence dissymmetry factor of 10 −2 is achieved.